Assessments for sport and athletic performance - Fukuda, David H. , 1980-
"Assessments for Sport and Athletic Performance is a resource for coaches and trainers that provides comprehensive, research-based tests and assessments. It includes information necessary for assessing body composition, strength, flexibility, balance,agility, speed, power, cardiovascular fitness, endurance, and other aspects of physical performance"-- Provided by publisher